The Reproductive Characters of Four Varieties of Groundnuts (Arachis hypogaea L.) - Lim, E. S.; Hamdan, Othman (1984)
The reproductive characters of 4 groundnut varieties, Nudong V-13, Matjam and Alabama. were studied. All varieties showed similar patterns of flowering, pegging and podding. Only 15 percent of the flowers produced developed mature pods. The .low yield ,was attributed to inefficient pollination and abortion of developing kernels due to adverse envzronmental mfluences.